Layanan Telemedicine Terintegratif Dokter dan Apoteker bagi Penderita Covid-19 di Lingkungan Paroki Kristus Raja Surabaya - Caroline Caroline; Senny Yesery Esar; Martha Ervina; Wuryanto Hadinugroho; Steven Steven; Yudhikuari Sincihu; Laura Wihanto (Jurnal Abdimas Kesehatan (JAK), 2022)
The global pandemic related to the coronavirus (2019-nCoV) continues to hit the world, including Indonesia until the end of 2021. The efforts to improve health services were carried out by various parties, including by members of the King of Christ Parish church as part of the Surabaya community. From this parish in July 2021, 301 people were sick with COVID-19 and almost 11% of them died. The public and health services were panicked by the occurrence of a wave of viral mutations, with the increasing of sufferers and high mortality rates. Integrated telemedicine services between doctors and pharmacists are one of the best options to prevent transmission and severity to support patient recovery rates. With telemedicine, health care needs are individualized and patient development is more controlled. The method was carried out through direct consultation between doctors, pharmacist, and patients, using the whatsapp call platform. Monitoring of patients was continued by pharmacist using the whatsapp message platform until the patient was cured. If necessary, consultation with the doctor could be carried out again during the patient’s healing process.  The research show that there is an integration of doctor and pharmacist services in telemedicine for COVID-19 patients in diagnosing, determining the best supporting drugs and therapies for the patients. Quantitatively, there was a decrease in the mortality rate, an increase in patient compliance and recovery. As an additional indicator, the residents welcome the integrated services that are carried out and can be developed for other health services.